Kajian literatur tentang pengaruh kualitas produk terhadap keputusan pembelian konsumen - Pratiwi, Firola; Puspita, Febi; Saputri, Rani (Journals of Indonesian Multidisciplinary Research, 2024)
Product quality is one of the key factors influencing consumer purchasing decisions, especially in an increasingly competitive market. This study aims to systematically review research trends, methods, variables, and analytical tools used in studies examining the influence of product quality on consumer purchasing decisions. A Systematic Literature Review (SLR) was conducted on 40 articles published between 2019 and 2024. The results show that product quality and price are the most frequently used variables in previous studies. Most of the research applied a quantitative approach, with SPSS and linear regression being the dominant analytical tools. In addition, research trends over the past five years indicate a shift toward exploring contextual variables such as social media, risk perception, and sustainability preferences. These findings provide valuable insights for researchers and business practitioners to design marketing strategies that align with evolving consumer behavior and product quality expectations.